Expression of long noncoding RNAs in cancer‐associated fibroblasts linked to patient survival in ovarian cancer. Issue 5 (28th March 2020) - Colvin, Emily K.; Howell, Viive M.; Mok, Samuel C.; Samimi, Goli; Vafaee, Fatemeh
Abstract: Cancer‐associated fibroblasts (CAFs) are the most abundant cell type in the tumor microenvironment and are responsible for producing the desmoplastic reaction that is a poor prognostic factor in ovarian cancer. Long non‐coding RNAs (lncRNAs) have been shown to play important roles in cancer. However, very little is known about the role of lncRNAs in the tumor microenvironment. We aimed to identify lncRNAs expressed in ovarian CAFs that were associated with patient survival and used computational approaches to predict their function. Increased expression of 9 lncRNAs and decreased expression of 1 lncRNA in ovarian CAFs were found to be associated with poorer overall survival. A "guilt‐by‐association" approach was used to predict the function of these lncRNAs. In particular, MIR155HG was predicted to play a role in immune response. Further investigation revealed high MIR155HG expression to be associated with higher infiltrates of immune cell subsets. In conclusion, these data indicate expression on several lncRNAs in CAFs are associated with patient survival and are likely to play an important role in regulating CAF function. Abstract : This manuscript shows that long noncoding RNAs (lncRNAs) are heterogeneously expressed in ovarian cancer‐associated fibroblasts and expression differences in several lncRNAs are associated with differences in patient survival. Expression profiles were analyzed from 67 microdissected ovarian cancer‐associated fibroblast samples, one of the largest cohorts available. One lncRNA, MIR155HG, was associated with increases in tumor‐infiltrating lymphocytes.